Effect of high blood cortisol concentration on the spectroscopically determined second-ary structure of proteins and lipid balance on the example of elite women volleyball players - Depciuch, J.; Czarny, W.; Szuszkiewicz, W.; Reich, A.; Klebowski, B.; Bajorek, W.; Plonka, A.; Maciejewska-Skrendo, A.; Luszczewska-Sierakowska, I.; Cebulski, J.; Król, P. (Acta Kinesiologica, 2022)
Cortisol is a stress hormone that plays a crucial role in the balance between phospholipids and lipids levels. In consequence, it affects the secondary structure of proteins. Currently cortisol concentration in serum is determined by a biochemical analysis. A new optical method to estimate the stress level is proposed in this work. Infrared and Raman spectroscopies were used to determine the quantitative and qualitative changes in lipids and proteins fractions in the function of cortisol concentration in 49 samples of serum collected from volleyball players at various stages of preparation for the competition. With the cortisol level increase, a decrease of structures related to PO2- phospholipid groups and amides III and I bonds was noticed in the Raman spectra. The differences in absorbance visible in the FTIR spectra, were not statistically significant. However, the calculated absorbance ratios between the peaks related to vibrations of the lipid functional groups and amide I show, that with the increase of cortisol concentration, the increase of the amount of lipids and the decrease of the amount of proteins was observed in transmission spectra. Pearson correlation test presented positive correlations between phospholipid and protein levels and between cortisol concentration and phospholipids in transmittance spectra. Negative correlations between cortisol concentration, protein and phospholipid levels were observed in the Raman spectra. Obtained results showed, that using Raman spectroscopy the effect of increased cortisol concentration on proteins, phospholipids and lipids is directly visible. in the case of FTIR spectroscopy, one had to calculate the ratios between CH2 and CH3 lipids vibrations (2957 cm-1, 2920 cm-1, 2872 cm-1) and amide I (1654 cm-1), to show differences in the cortisol concentration in serum. These results suggest, that Raman spectroscopy is a more promising technique to obtain an information about cortisol levels in serum.